Studi Ketahaanan Coating Ni Yang Di Bentuk Melalui Proses Elektroplating Terhadap Beban Panas Kejut - Setiawan, Muh Taufiq (2016)
Many common carbon steel as a construction material engineering, but the use at high temperatures such as natural gas pipelines, turbine components, hot-work tool steels are still not widely found. This is because the heat resistance of low carbon steel. The purpose of this study was to develop a layer of Ni in carbon steel with electroplating processes, and continued by knowing the heat resistance coating. This research was conducted by using a material of low carbon steel St 40 as a substrate with a diameter of 16 mm at a thickness of 3 mm and a mixed solution of nickel sulfate, nickel chloride and boric acid as a coating material Ni. The electroplating process using a voltage of 2.1 volts with a long dip 2 hours. To determine the heat resistance of the product coating then after the electroplating process, the specimen is inserted in a heating oven with 5 variations of temperature (500°C, 600°C, 700°C, 800°C and 900°C) for 30 minutes and then cooled rapidly with water. Characteristics of the product is done by testing a micro photograph and testing of mechanical properties is done by micro vickers to determine the hardness of the coating Ni. The test results of micro photo thickness of Ni are heated with temperature variation shows that the thickness of the electroplating layer at a temperature of 500°C has the highest thickness of 24.95 μm, 22.50 μm at a temperature of 600°C, 700°C temperature of 20.40 μm, a temperature of 800°C at 18.86 μm, and a temperature of 900°C at 17.87 lm. Hardness testing on specimens that have been heated Ni layer showed that on heating to 500°C to produce the highest hardness of 215.3 HV, heating 600°C yield of 177.4 HV hardness, heating 700°C yield of 153.0 HV hardness, heating 800°C produce violence amounted to 131.6 HV, and heating at 900°C to produce 100.3 HV hardness. Based on testing of micro photograph and micro vickers the Ni coating, the heating process has led to a reduction in the thickness and the reduction of violence.